PENGARUH SUDUT PAHAT PADA PENGGURDIAN KOMPOSIT SERAT DAUN NANAS / TERMOPLASTIK PADA PEMBENTUKAN DELAMINASI - Zulkarnain Zulkarnain; Ismet Hari Mulyadi; Jupri Jupri; Siswandi B (POLITEKNIK NEGERI BENGKALIS, 2023)
This study aims to determine the effect of the Gurdi tool angle on delamination in composite laminates in the formation of delaminations. The spacing of the selected reinforcing fibers was 2.4 and 6 mm in a composite laminate of ethylene vinyl acetate (EVA) polymer matrix with reinforcing fibers from pineapple leaves. The method used in composite fabrication is hand lay-up, namely by direct casting on three layers of fiber that has been woven and tied to the sides of the mold. For cutting speed, Vf 72 mm / min, using a chisel with a diameter of 8 mm with a tool angle of 70o and 118o. Delamination was determined using the Feda method. The delamination sections were observed using a digital microscope and then processed using AutoCAD to measure Dmax and Ad. The delamination ratio in the top hole for the tool diameter of 8mm with a 70° angle at the variation of the distance of 2 mm, 4 mm and 6 mm were 1.268, 1.224 and 1.192 for the bottom hole were 1.078, 1.042 and 1.029, respectively. Meanwhile, the ratio of delamination in the upper hole for a tool diameter of 8mm with an angle of 118° at a distance variation of 2mm, 4mm and 6mm were 1.194, 1.194, 1.158 for the bottom hole, respectively, 1.046, 1.042 and 1.038.